PENGEMBANGAN MEDIA KARTU KATA BERBASIS KEARIFAN LOKAL PADA PEMBELAJARAN BAHASA INDONESIA UNTUK PENINGKATAN KEMAMPUAN LITERASI MEMBACA DI SEKOLAH DASAR - Ida Frestiyana; Wahyudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This research aims to find out the steps for media development, find out the validity of learning media, and find out the level of effectiveness of word card as learning media based on local wisdom in Temanggung City to improve the reading literacy skills of grade 1 elementary school students. The method used in this research is R&D using the ASSURE development model, namely: Analyze Learner, State Objective, Select Media and Materials, Utilize Media and Materials, Require Learner Participation, and Evaluation and Revise. The result of validation from material experts, the word card as learning media received the score of 100% so it is included in the very high category. The validation results from learning media experts obtained a feasibility score of 95%, so it is included in the very high category. Also, the validation results from learning design experts got a score of 93% so it is included in the very high category. The results of the Paired Samples Test showed that the sig (2-tailed) value is 0.000 < 0.05, so it can be concluded that there is a real difference between the pretest results and the posttest results from assessing the reading literacy skills of grade 1 elementary school students. So that the word card as learning media based on local wisdom in Temanggung City has proven to be valid and effective in improving the reading literacy skills of grade 1 students at SD Negeri 1 Tepusen.